2011
DOI: 10.1007/978-3-642-19789-5_4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Street Networks of Navteq and OSM in Germany

Abstract: In Germany, the data of the Open Street Map project has become available as an alternative to proprietary road networks in commercial business geomatics software, and their customers are wondering whether the quality may be sufficient. This paper describes an implemented methodology to compare OSM street data with those of Navteq for all populated roads in Germany. As a unique feature, the presented methodology is based on a matching between the street objects of OSM and Navteq, and all steps are fully automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 4 publications
4
93
0
Order By: Relevance
“…Further, comparing the completeness of OSM roads for the entire U.K., Haklay [43] found that at the time, OSM roads accounted for 69% of OS data with as much as 25% better coverage using OSM data in some areas. A similar high correspondence (97% in urban areas) was reported by Ludwig et al [44], comparing the completeness of road features (e.g., primary, secondary and cycle paths) in OSM with Navteq data in several German cities. With respect to the latter study in Germany, however, care must be taken when extrapolating the results of such studies to other cities, since, as Neis et al [45] suggests, Germany contains the most active OSM communities.…”
Section: Introductionsupporting
confidence: 84%
“…Further, comparing the completeness of OSM roads for the entire U.K., Haklay [43] found that at the time, OSM roads accounted for 69% of OS data with as much as 25% better coverage using OSM data in some areas. A similar high correspondence (97% in urban areas) was reported by Ludwig et al [44], comparing the completeness of road features (e.g., primary, secondary and cycle paths) in OSM with Navteq data in several German cities. With respect to the latter study in Germany, however, care must be taken when extrapolating the results of such studies to other cities, since, as Neis et al [45] suggests, Germany contains the most active OSM communities.…”
Section: Introductionsupporting
confidence: 84%
“…The authors have also investigated the impact of the number of contributors on positional accuracy, and estimated that high accuracy is achieved when there are at least 15 contributors per square kilometre. Works such as [2,12] have confirmed these observations for countries like France, Germany and Switzerland. Moving from accuracy to coverage of OSM data, a recent study by Zielstra et al [25] shows that coverage in Germany sharply decreases as we move away from city centres; Girres et al [2] also discovered a correlation between the number of OSM objects in an area and number of contributors in that area (i.e., areas with up to three contributors per square kilometre had ten times more contributions than areas with only one contributor, and 5 http://www.navteq.com/ areas with more than three contributors had up to hundred times more contributions).…”
Section: Background and Related Workmentioning
confidence: 64%
“…We did so by dividing Greater London in two: Inner London and Outer London, as depicted in Figure 11. 11 The distinction comes from the London Government Act 1963 12 where Inner London is defined as the richest area in Europe, albeit widespread poverty towards the East and South.…”
Section: Understanding Mediating Influencementioning
confidence: 99%
“…However, these need to be customized for different languages. The 'Levenshtein' algorithm [72] measures the similarity between two strings by calculating the least number of edits that is needed to modify one string to another [46,49,51,55,71]; whereas, 'similar_text' function is a much simpler and faster one, which returns the number of similar characters between the two strings [73]. Barron et al [74] have assessed the attributes and quantitative information of data.…”
Section: Attribute Accuracymentioning
confidence: 99%